2010
DOI: 10.1161/circulationaha.110.940288
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Denervation With Magnetic Nanoparticles

Abstract: Background-Prior studies indicated that ablation of the 4 major atrial ganglionated plexi (GP) suppressed atrial fibrillation. Methods and Results-Superparamagnetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…They demonstrated that botulinum neural toxin A selectively injected into the sinoatrial fat pad inhibited a decrease in sinus rate in response to vagus nerve stimulation, and suggested that botulinum toxin can inhibit ganglionic neurotransmission in the dog heart in situ. In a study by Yu et al 32 , a neurotoxic agent (N-isopropylacrylamide monomer) in the anterior right and inferior right GPs reduced GP activity with a subsequent increase in the AF threshold. In a recent study, Oh et al 33 investigated the short-to mid-term effects of GP suppression by botulinum toxin on AF inducibility in the dog.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They demonstrated that botulinum neural toxin A selectively injected into the sinoatrial fat pad inhibited a decrease in sinus rate in response to vagus nerve stimulation, and suggested that botulinum toxin can inhibit ganglionic neurotransmission in the dog heart in situ. In a study by Yu et al 32 , a neurotoxic agent (N-isopropylacrylamide monomer) in the anterior right and inferior right GPs reduced GP activity with a subsequent increase in the AF threshold. In a recent study, Oh et al 33 investigated the short-to mid-term effects of GP suppression by botulinum toxin on AF inducibility in the dog.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that autonomic innervation of the heart consists of a large neural network and GP serve as the integration centers in the neural network. 23,[27][28][29][30][31][32] The major atrial GP, targeted by botulinum toxin in this study, contain hundreds to thousands of autonomic neurons, mainly postsynaptic cholinergic neurons activated by presynaptic acetylcholine. The neural network controls the regional electrophysiological functions, such as the refractory period and dispersion of the refractoriness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In addition, magnetic guidance of nanoparticles has been previously shown as a viable drug delivery system, including its use to direct ganglionic plexus toxicity. 18 Heat-sensitive liposomes can be utilized to systemically administer a pharmacological payload but yet have a localized effect by only releasing that payload on heat activation. Liposomes are biologically inactive and have minimal toxic effects in humans; in our porcine model, animals were pretreated with medications because pigs may have an allergic reaction to the liposomes.…”
Section: Previous Investigations Into Ablation Of Nanoparticle-treatementioning
confidence: 99%
“…Interestingly, Yu et al11 have proposed a technique using injected iron-core nanoparticles to target the ganglionated plexi for ablation. The use of magnetic particles has a long history in medicine.…”
mentioning
confidence: 99%